THU0377 IMPACT OF FILGOTINIB ON STRUCTURAL LESIONS IN THE SACROILIAC JOINTS AT 12 WEEKS IN PATIENTS WITH ACTIVE AXIAL SPONDYLOARTHRITIS: MAGNETIC RESONANCE IMAGING DATA FROM THE DOUBLE-BLIND, RANDOMIZED TORTUGA TRIAL. (2nd June 2020) - Maksymowych, W. P.; Ǿstergaard, M.; Landewé, R. B. M.; Barchuk, W.; Liu, K.; Tasset, C.; Gilles, L.; Hendrikx, T.; Besuyen, R.; Baraliakos, X.
Abstract : Background: Filgotinib, an oral selective Janus kinase (JAK) 1 inhibitor, reduced disease activity and improved symptoms and inflammation of the sacroiliac joint (SIJ) and spine in patients with active axial ankylosing spondylitis (AxSpA) in the Phase 2 TORTUGA trial (NCT03117270 ). 1 The effects of JAK inhibitors on structural lesions in active AxSpA are unknown and optimal methods for image analysis of structural disease progression are not established. Objectives: The aim of this post hoc analysis was to evaluate the effects of filgotinib on magnetic resonance imaging (MRI) measures of structural changes in the SIJ in patients from the TORTUGA trial, as assessed by Spondyloarthritis Research Consortium of Canada (SPARCC) SIJ Structural Scores (SSS). Methods: TORTUGA was a multicenter, double-blind, randomized trial of 116 patients with active AxSpA treated with filgotinib 200 mg (n=58) or placebo (n=58) once daily for 12 weeks. MRI was conducted at baseline and Week 12 (or early discontinuation visit). MRIs were re-evaluated post hoc by two independent experts (blinded to time point and assigned treatment) to determine SPARCC SSS; inter-reader discrepancies were resolved by an independent adjudicator. Observed changes from baseline were evaluated using analysis of covariance with factors for treatment, baseline value, and randomization stratification. Least-squares mean changes from baseline and between-group differences with 95% confidence intervals were calculated. Results: MRI scans from 87 patients with an evaluable MRI at baseline and Week 12 (or early termination visit) were re-evaluated (48 filgotinib, 39 placebo). Erosion scores decreased in the filgotinib group and increased in the placebo group (p=0.02 for between-group difference; Table 1 ; Figure 1a ). Backfill scores increased in the filgotinib group but not in the placebo group (p=0.005; Table 1 ; Figure 1b ). There was no statistically significant between-group difference in SSS total ankylosis (p=0.46) or fat lesion (p=0.17) changes from baseline (Table 1 ). Conclusion: In addition to previously reported decreases in SPARCC inflammation, filgotinib was associated with significant reduction in SIJ erosion scores and increase in backfill scores at Week 12 of the TORTUGA trial, versus placebo. Long-term effects are to be determined. References: [1]van der Heijde D, et al. Lancet 2018;392:2378–87. Acknowledgments: We thank Robert Lambert for his review of the MRI scans in the role of adjudicator. The TORTUGA trial was sponsored by Galapagos NV and co-funded by Galapagos NV and Gilead Sciences. Medical writing support was provided by Hannah Mace MPharmacol, CMPP (Aspire Scientific Ltd, Bollington, UK) and funded by Galapagos NV (Mechelen, Belgium). Disclosure of Interests: Walter P. Maksymowych Grant/research support from: AbbVie, Novartis, Pfizer, and UCB, Consultant of: AbbVie, Boehringer Ingelheim, Celgene, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Employee of: Chief Medical Officer of CARE Arthritis Limited, Speakers bureau: AbbVie, Janssen, Novartis, Pfizer, and UCB, Mikkel Ǿstergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Merck, and Novartis, Consultant of: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Robert B.M. Landewé Consultant of: AbbVie; AstraZeneca; Bristol-Myers Squibb; Eli Lilly & Co.; Galapagos NV; Novartis; Pfizer; UCB Pharma, William Barchuk Shareholder of: Gilead Sciences Inc and Eli Lilly, Employee of: Current employee of Gilead Sciences Inc and a former employee of AbbVie, Eli Lilly, and Johnson & Johnson, Ke Liu Shareholder of: Gilead Sciences Inc (stockholder), Employee of: Gilead Sciences Inc, Chantal Tasset Shareholder of: Galapagos (share/warrant holder), Employee of: Galapagos, Leen Gilles Consultant of: Galapagos, Thijs Hendrikx Shareholder of: Galapagos (share/warrant holder), Employee of: Galapagos, Robin Besuyen Shareholder of: Galapagos, Employee of: Galapagos, Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen